Analysis of Apron Movement Control Coordination in Plotting Parking Stands to Support Flight Safety at Adi Soemarmo Airport Solo - May Sekar Wijaya; Djoko Widagdo (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Apron Movement Control (AMC) at Adi Soemarmo International Airport is aimed at monitoring all traffic movements in the apron area consisting of air traffic, vehicles and personnel at the airport, supervision here provides the meaning of the steps needed to prevent accidents from happening. in this case the case of a collision between the three elements forming the apron traffic, where they carry out joint activities. In addition, supervision is also intended so that traffic control can take place smoothly, if the parking stand plotting is not in accordance with the existing SOP, plotting errors will occur. This research is to find out the role of AMC in coordinating Plotting Parking Stands to support flight safety and to find out what are the constraints of AMC in coordinating Plotting Parking Stands to support flight safety at Adi Soemarmo Solo Airport. This research is a qualitative research. Data collection techniques used are observation, interviews and documentation. Observation of this study by direct observation of the handling of AMC coordination in plotting parking stands at Adi Soemarmo International Airport. The interviews in this study were Apron Movement Control (AMC) unit officers, tower unit officers and Ground Handling officers at Adi Soemarmo International Airport. Data analysis consists of data reduction (data reduction), data presentation (data display) and drawing conclusions (drawing/ verification). The validity of the data using triangulation techniques. The results of this study can be concluded that the important role of AMC in coordinating plotting parking stands is very large and has great responsibility in each of its operations, one of which is regarding plotting parking stands. As well as coordination carried out by AMC with towers and ground parties. One of the obstacles faced by Apron Movement Control was the implementation of the parking stand plotting procedure carried out by AMC for the tower and ground which had to be taken by one of the parties due to communication constraints carried out by the relevant parties, because if the plane is delayed, damaged or there are many requests it must be coordinated swiftly and responsively with competent personnel as stated by AMC.